1986
DOI: 10.1021/jm00156a035
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationships for the competitive angiotensin antagonist [sarcosine1, O-methyltyrosine4]angiotensin II (sarmesin)

Abstract: Analogues of the competitive angiotensin antagonist [Sar1,Tyr(Me)4]ANG II (sarmesin) in which the sarcosine-1, O-methyltyrosine-4, and phenylalanine-8 residues were modified have been synthesized by the solid-phase method. The agonist and antagonist potencies of the 23 peptides synthesized were determined in the rat isolated uterus assay. At position 1, replacement of Sar with Asp, Ala, or Pro gave inactive analogues, and deletion of the N-terminal amino acid produced inactive heptapeptides for all analogues i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
14

Year Published

1986
1986
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 0 publications
0
16
0
14
Order By: Relevance
“…Analyses of the effects of different ANG II analogs bearing single or multiple modifications indicated that an electrostatic interaction between the ANG II COOH-terminal carboxylate group and the receptor is an important factor for high-affinity binding (100) and that the peptide's Arg 2 , Tyr 4 , and His 6 side chains are also important for high-affinity binding (31,178,239,240). On the other hand, replacements of Tyr 4 and mainly Phe 8 by aliphatic residues were shown to generate competitive antagonists, thus attesting to the importance of these aromatic residues for receptor activation (70,247). The Val 3 , Ile 5 , and Pro 7 residues were found to be neither crucial for binding nor for activation.…”
Section: A Receptor Binding and Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of the effects of different ANG II analogs bearing single or multiple modifications indicated that an electrostatic interaction between the ANG II COOH-terminal carboxylate group and the receptor is an important factor for high-affinity binding (100) and that the peptide's Arg 2 , Tyr 4 , and His 6 side chains are also important for high-affinity binding (31,178,239,240). On the other hand, replacements of Tyr 4 and mainly Phe 8 by aliphatic residues were shown to generate competitive antagonists, thus attesting to the importance of these aromatic residues for receptor activation (70,247). The Val 3 , Ile 5 , and Pro 7 residues were found to be neither crucial for binding nor for activation.…”
Section: A Receptor Binding and Activationmentioning
confidence: 99%
“…Later on, sarmesin, a potent antagonist with hydroxymethylated Tyr 4 ([Sar 1 ,Tyr(Me) 4 ]-ANG II), was described (252). Combined modifications on both Tyr 4 and Phe 8 were shown to be nonadditive, generating antagonists of lower potencies (70,247).…”
Section: B Antagonism By Ang II Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…a competitive inhibitor of angiotensin II binding would be either competitive or non-competitive with ATP in a random mechanism, but would be uncompetitive with ATP in the ordered reaction. We have tried sarmesin (a non-phosphorylatable angiotensin II analogue; Goghari et al, 1986) and tyrphostin (a synthetic compound reported to be a competitive inhibitor of protein substrate binding to the EGF receptor; Gazit et al, 1989), but both were found to be non-competitive with angiotensin II in the presence of protamine (results not shown).…”
Section: Substratementioning
confidence: 99%
“…Επιπλέον το αμινοξύ στη θέση 1 συντελεί στη σταθεροποίηση της στερεοχημικής διαμόρφωσης του μορίου της αγγειοτενσίνης II με τις ηλεκτροστατικές αλληλεπιδράσεις, οι οποίες αναπτύσσονται μεταξύ του Ν-και C-τελικού αμινοξέος [280] . Μία άποψη για το ρόλο που διαδρα ματίζει το Ν-τελικό αμινοξύ στην πεπτιδική αλληλουχία του μορίου της Α II είναι ότι, απωθεί την πλευρική αλυσίδα της Tyr 4 προς την πλευ ρική αλυσίδα της His 6 διευκολύνοντας έτσι τις αλληλεπιδράσεις μεταξύ των δύο αυτών αρωματικών αμινοξέων [297].…”
Section: α23 το σύμπλεγμα αγγειοτενσίνης II -υποδοχέαunclassified